The relation between the epistemological beliefs of teachers and students and their behavior in educational practice - Maravilla, Jaime (2015)
This article analyzes the relation of the epistemological beliefs of students and teachers and the actions deployed in the classroom. The framework is the study of personal epistemology, which was developed, among other researchers, by Hofer, Pintrich and Schommer. The research method was, within the qualitative paradigm, through case studies, given the interest in describing the phenomenon in a specific scenario. The results show the epistemological beliefs of teachers and students, the events that make them evident and its relationship with the behaviors shown in the classroom. The role of pedagogical beliefs as mediation between personal epistemology of educational actors and their practice are described and, finally, the relation between beliefs and educational practice is illustrated by analyzing specific class events and the justification expressed by teachers and students about their actions in the classroom.